Optimization of methodology with solid state nuclear track detector (SSNTD) - Reginaldo Anderson Silva; Ademar de Oliveira Ferreira (Brazilian Journal of Radiation Sciences, 2021)
The present study aims to optimize the passive methodology with Solid state Nuclear Track Detector (SSNTD) called the sealed can technique in the physics laboratory of the Federal Institute of Paraná - Telêmaco Borba Campus. The work used a polycarbonate polymer as detector because it is a polycarbonate of national manufacture and of low cost. A factorial design was carried out with three variables, one with two levels, one with three levels and one with four levels, totaling 24 experiments. The factors evaluated were the volume of the sealed can (1000 ml, 300 ml and 200 ml), chemical attack time (1 h, 2 h, 3 h and 4 h) and the chemical attack solution (solution A, PEW-40 and solution B, KOH- 70). In all 24 experiments the can was sealed with aliquots of the same geological sample for 38 days before chemical revelation and counting of the tracks. The results showed that solution B can be discarded due to the low concentration of tracks obtained in all 12 experiments performed with it. The results for solution A showed that the highest concentration of tracks is obtained for the chemical revelation time of 3 h, regardless of volume, and that the volume of 300 ml is the best result. Thus the conclusion of the study is that solution A in the volume of 300 ml and with chemical revelation time of 3 h is the optimal procedure for the development of the tracks.